(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The examination and surgical treatment of 1759 patients with acute appendicitis are presented. Analysing the Alvarado scale using the possibility of diagnosing acute appendicitis can help reduce the number of diagnostic errors and unjustified surgical interventions if acute appendicitis is suspected.